Drainage of an ice-dammed lake through a supraglacial stream: hydraulics and thermodynamics - C. Ogier (Copernicus Publications, 2021)
The glacier-dammed Lac des Faverges, located on Glacier de la Plaine Morte (Swiss Alps), has drained annually as a glacier lake outburst flood since 2011. In 2018, the lake volume reached more than 2 × 106 m3, and the resulting flood caused damage to the infrastructure downstream. In 2019, a supraglacial channel was dug to artificially initiate a surface lake drainage, thus limiting the lake water volume and the corresponding hazard. The peak in lake discharge was successfully reduced by over 90 % compared to 2018. We conducted extensive field measurements of the lake-channel system during the 48 d drainage event of 2019 to characterize its hydraulics and thermodynamics. The derived Darcy–Weisbach friction factor, which characterizes the water flow resistance in the channel, ranges from 0.17 to 0.48. This broad range emphasizes the factor's variability and questions the choice of a constant friction factor in glacio-hydrological models. For the Nusselt number, which relates the channel-wall melt to the water temperature, we show that the classic, empirical Dittus–Boelter equation with the standard coefficients does not adequately represent our measurements, and we propose a suitable pair of coefficients to fit our observations. This hints at the need to continue research into how heat transfer at the ice–water interface is described in the context of glacial hydraulics.